Volumetric Image Analyzer for Medical Applications (VIAMA) - Clemente, Rodiezon (2002)
VIAMA is a software that will collect and convert slices of two-dimensional images into a single three-dimensional image known as a volumetric image. Volumetric images are three-dimensional image array corresponding to a stack of two-dimensional slices or cross section of an object. The 3D image produced must be viewed and rotated. The generated volumetric image will be useful for medical analysis of internal body organs. Sources of image slices could be taken from CT Scans or MRI Scans. Specifically VIAMA will use slides of JPEG images as an input to produce a three-dimensional volumetric image. Image slices should be produced from some other device and be converted to JPEG file format. VIAMA will be implemented using Java and should be portable with different platforms. The software will be capable also of viewing each slide and creating patient's personal profile.